(Learning with a difference) Composition strategies primary 6 - Henderson, Diane (Learners Press Private Singapore, 2009)
Composition Strategies Primary 6 provides students with effective techniques to improve their writing skills by focusing on structure, creativity, and clarity. It offers step-by-step guidance on crafting well-organized compositions, helping students express their ideas confidently and coherently.